Rancangan Dan Implementasi Virtual Tour 360 Berbasis Realitas Virtual Untuk Pemandu Kampus Digital (Studi Kasus : Universitas Hindu Indonesia) - I Putu Indrayana Putra; I Kadek Andy Asmarajaya; I Putu Mahendra Adi Wardana (RESI : Jurnal Riset Sistem Informasi, 2026)
The advancement of information technology encourages higher education institutions to adopt interactive and immersive digital promotional media. The Indonesian Hindu University does not yet have a Virtual Reality-based platform capable of providing a comprehensive visualization of its campus environment. This study aims to design and implement a 360° Virtual Tour application as a digital campus guide using the Multimedia Development Life Cycle (MDLC) method, which consists of concept, design, material collecting, assembly, testing, anddistribution stages. The application was developed as a web-based system using 3DVista and PTGui software to generate interactive 360° panoramas. System testing was conducted through alpha testing by media experts using the Guttman scale, resulting in a 100% validation score, indicating that the application is highly valid. Beta testing involving 20 respondents using a Likert scale showed a feasibilityscore of 85.4%, categorized as highly feasible. The results indicate that the application provides an interactive and informative experience and is effective as a digital campus promotion and guidance tool